Phenobarbitone for the Management of Neonatal Seizures - A Single Center Study - Rabindran Rabindran; Hemant Parakh; Ramesh J K; Prashant Reddy (International Journal of Medical Research and Review, 2015)
Introduction: Phenobarbitone is currently the drug of choice for neonatal seizures. In this study we analyzed the effect of Phenobarbitone in the management of neonatal seizures.Objectives: To review the cumulative dosage, efficacy of phenobarbitone and need for second and third anti-seizure medication in the treatment of neonatal seizures.Methods: This is a cross sectional retrospective observational study from January-2011 to December-2014. Based on clinical observation, anticonvulsant efficacy was assessed. Need for second Ant seizure drug and Cumulative loading dose were studied. All babies admitted with clinical seizures and those developing seizures during hospitalization who were treated with Phenobarbitone as the first drug were studied.Interventions: Management of neonatal seizures as per standard unit protocol. Study was approved by the Institutiona::l Ethical Committee.Statistical Analysis: All the data were collected in validated preformatted proforma sheet and analysed using appropriate statistical methods.Results: 117 babies received phenobarbitone during the study period. Majority (49.57%) of seizures occurred during day 1 of life. HIE was the commonest cause noted in 42.73%. Seizure control with 20 mg/kg loading dose of phenobarbitone was noted in 40.17% of pateints & Seizure control with 30 mg/kg loading dose of phenobarbitone was in 19.65%. Seizure control with phenobarbitone as monotherapy was 59.82% and as combinant therapy with Levetiracetam was 32.47%.Conclusion: Phenobarbitone had significant seizure control both as monotherapy and along with levetiracetam as combinant therapy.